2015
DOI: 10.1097/mca.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue thickness can be used to predict major adverse cardiac events

Abstract: Increase in EAT thickness independently predicts adverse cardiac events including MI and cardiovascular death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…49,51,53 Similarly, an increased amount of fatty tissue surrounding the heart has been shown to predict major adverse cardiac events including myocardial infarction and death in subjects with acute coronary syndromes, as well as in those with suspected coronary artery disease. [54][55][56] The link between atrial fibrillation and EAT could be explained by the concomitant coronary artery disease of these patients. However, new research has shown that there is an association between AF and epicardial fat in subjects who are free of cardiovascular disease, independent of classical cardiovascular risk factors and coronary atherosclerosis.…”
Section: Epicardial Fat Determination With Noninvasive Imaging Technimentioning
confidence: 97%
“…49,51,53 Similarly, an increased amount of fatty tissue surrounding the heart has been shown to predict major adverse cardiac events including myocardial infarction and death in subjects with acute coronary syndromes, as well as in those with suspected coronary artery disease. [54][55][56] The link between atrial fibrillation and EAT could be explained by the concomitant coronary artery disease of these patients. However, new research has shown that there is an association between AF and epicardial fat in subjects who are free of cardiovascular disease, independent of classical cardiovascular risk factors and coronary atherosclerosis.…”
Section: Epicardial Fat Determination With Noninvasive Imaging Technimentioning
confidence: 97%
“…23 Also, Tanindi et al demonstrated that EAT thickness measured by echocardiography is independently associated with MI. 24 Epicardial fat could provide additional evidence of future cardiac events in patients with acute coronary syndromes (ACS). It is well known that an increase in systemic inflammatory status leads to a lower prognosis in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…EAT thickness can be used as a predictor of MACE, including MI and sudden death. 24 In addition, it has been shown that an increased volume of epicardial adipose tissue predicted MI or cardiovascular death in patients suspected of CAD. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent study, an initial thickness of EAT of more than 7 mm was shown to be a significant predictor of MACE, death, revascularization, and myocardial infarction. 11 However, echocardio-graphy can only determine the diameter of EAT, while CT provides the advantage of more reliable quantification and at the same time, an assessment of plaque vulnerability.…”
Section: Epicardial Adipose Tissue and Coronary Artery Diseasementioning
confidence: 99%